Axial Load-Axial Deformation Behaviour of SCC Columns Reinforced with Steel Tubes. (August 2018) - Alhussainy, Faez; Sheikh, M. Neaz; Hadi, Muhammad N.S.
Abstract: A simplified analytical model has been developed for the axial load-axial deformation behaviour of self-compacting concrete (SCC) columns reinforced with steel tubes. The developed analytical model takes into account the contribution of the steel tubes, unconfined concrete cover, confined concrete core and confined concrete inside the steel tube. The results of the analytical model have been compared with experimental results of four SCC column specimens. The results of the analytical model are in good agreement with the experimental results. A parametric study has been conducted to investigate the influences of the compressive strength of SCC, tensile strength of steel tube, wall thickness of steel tube and pitch of steel helix on the axial load-axial deformation behaviour of SCC columns reinforced with steel tubes. The ductility of SCC columns has been found to be significantly influenced by the increase in the compressive strength of SCC and the pitch of steel helix.